2009
DOI: 10.1002/pits.20369
|View full text |Cite
|
Sign up to set email alerts
|

Group counseling in the schools

Abstract: Group counseling is an effective intervention when working in a school setting. In this article, the authors discuss the different kinds of groups offered in schools, types of group interventions, strategies to use in forming groups, and how to collaborate with others in the school. Because leading groups in schools is a specialized skill, the authors suggest that group leaders form collaborative relationships with others in the school, allot sufficient time for group counseling, advocate to change policies th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 12 publications
1
10
0
1
Order By: Relevance
“…Group interventions can be delivered to multiple adolescents within a limited timeframe, thus maximizing efficiency while not compromising effectiveness (Pe´russe, Goodhough, & Lee, 2009). While this is convenient in terms of time, space, staffing, and financial considerations, groups also allow professionals to begin work with young people sooner to prevent the escalation of disruptive behaviours, which could lead to eventual exclusion during a long wait period (Mennuti, Freeman, & Christner, 2006).…”
Section: Group Work Using Cognitive Behavioural Approachesmentioning
confidence: 99%
“…Group interventions can be delivered to multiple adolescents within a limited timeframe, thus maximizing efficiency while not compromising effectiveness (Pe´russe, Goodhough, & Lee, 2009). While this is convenient in terms of time, space, staffing, and financial considerations, groups also allow professionals to begin work with young people sooner to prevent the escalation of disruptive behaviours, which could lead to eventual exclusion during a long wait period (Mennuti, Freeman, & Christner, 2006).…”
Section: Group Work Using Cognitive Behavioural Approachesmentioning
confidence: 99%
“…In Indonesia, group counseling is considered and viewed as important, more effective and efficient than individual counseling since the ration between the counselor and counselee at school is 1: 150 (Kementerian Pendidikan Nasional, 2014). Previous studies show that group counseling is proven to be effective than individual counseling to be applied in a school setting (Pérusse, Goodnough, & Lee, 2009). Similar studies report that group counseling/psychotherapy is more effective than individual counseling in addressing attention disorder and hyperactive (Philipsen et al, 2015).…”
Section: Introductionmentioning
confidence: 88%
“…In addition, Schaefer (1999), observing individual short‐term group counseling, found that the treatment can be most effective in helping children develop adaptive processes for coping with a range of problems. Many studies suggested that group counseling was an effective intervention when working in a school setting (Crespi, 2009; Perusse, Goodnough, & Lee, 2009), and that it was helpful to students (Whiston & Quinby, 2009). Group counseling provided an excellent forum to promote student‐to‐student learning and was often experienced by students as an enjoyable and meaningful aspect of school.…”
Section: Functional Group Counseling Interventionmentioning
confidence: 99%